Several digital timers and clocks for desktop computers - WenJun Zhang (Computational Ecology and Software, 2024)
Several digital timers and clocks for desktop computers were developed in present study. Digital timers are used for time control in scientific experiments, dissertation defensing, work debriefing, academic lecture, student teaching, etc. Digital timer-counter and clocks are used for field sampling, field observation, ecological experiments, etc. All digital timers and clocks were packed and can be freely downloaded.